2021
DOI: 10.1093/jcag/gwab002.233
|View full text |Cite
|
Sign up to set email alerts
|

A235 Effects of Sacral Photobiomodulation on the Autonomic Nervous System in Patients With Colonic Dysmotility

Abstract: Background Patients with chronic refractory constipation show colon dysmotility, including impaired coordination of descending colon-sigmoid colon-rectum-anal sphincter motor functions; this may involve slow colonic transit and colo-anal dyssynergia. Impaired neuronal communication between the sacral defecation center and the distal colon may be causative. In addition, patients with lumbosacral neurological conditions (with lower back pain) may not be able to evoke an effective defecation ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The symptoms of FCC improved from 13 to 8 on a 20-point scale in a study conducted by Chen et al (2021) on 41 patients who underwent LLLT treatment using red LED light at 660 nm wavelength for 10 min, infrared LED light at 840 nm wavelength for 10 min, followed by infrared laser light at 825 nm wavelength for 20 min, eight sessions over 3 weeks. Also, Chen et al concluded that LLLT therapy of a patient who had been unable to create spontaneous bowel motions resulted in the patient being able to have full evacuations after only eight LLLT sessions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of FCC improved from 13 to 8 on a 20-point scale in a study conducted by Chen et al (2021) on 41 patients who underwent LLLT treatment using red LED light at 660 nm wavelength for 10 min, infrared LED light at 840 nm wavelength for 10 min, followed by infrared laser light at 825 nm wavelength for 20 min, eight sessions over 3 weeks. Also, Chen et al concluded that LLLT therapy of a patient who had been unable to create spontaneous bowel motions resulted in the patient being able to have full evacuations after only eight LLLT sessions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%